PRE-READING SKILL THROUGH BULLETIN BOARD MEDIA FOR CHILDREN AGE 5-6 YEARS - Elva Dwi Ratnasari; Warananingtyas Palupi; Muhammad Munif Syamsuddin (Universitas Sebelas Maret, 2020)
This study aimed to improve the ability of pre-reading by using bulletin boards for children aged 5-6 years. This research was a Classroom Action Research (CAR) which consists of two cycles. Each cycle consists of two meetings and four stages are carried out, namely planning, implementing the action, observing and reflecting. The subjects of this study were children aged 5-6 years at TK Khadijah III Pucung for the 2018/2019 academic year with 14 children. Data collection techniques using observation data, interviews, tests and documentation. The validity test of the data through triangulation of sources and triangulation of techniques. The data analysis technique used is qualitative analysis and quantitative analysis. The results of this classroom action research indicate an increase the pre-reading ability of each cycle. The pre-action completeness percentage obtained a result of 35% with 5 children who got a complete score. In the first cycle it increased by a percentage of 57% or 8 children who got a complete score, and in the second cycle it increased by a percentage of 86% or 12 children who got it. Based on the description above, the results of classroom action research carried out in two cycles can be concluded that bulletin board media can improve the pre-reading ability of group B at TK Khadijah III Pucung Academic Year 2018/2019.